Photosensitive resin, photosensitive metal slurry and application thereof, light-cured metal component and preparation method and application thereof

By using a specific formula of photosensitive resin and photosensitive metal paste, combined with 3D printing and sintering treatment, the residual carbon problem in photocuring technology is solved, and the mechanical properties of the photocured metal materials are comparable to those of forged metals and excellent tribological properties are achieved.

CN119638912AActive Publication Date: 2025-03-18YANTAI ZHONGKE RES INST OF ADVANCED MATERIALS & GREEN CHEM ENG +2
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411642959.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Photocuring technology molding metal materials have many technical difficulties in achieving mechanical properties and functionality comparable to forged metals, especially because the photosensitive resin decomposition is incomplete during degreasing, resulting in residual carbon problems, affecting the metal properties after sintering.

Method used

Photocured metal components are prepared by using a photosensitive metal paste prepared by a specific photosensitive resin through the steps of 3D printing, degreasing treatment, residual carbon removal and sintering treatment. The photosensitive resin monomer includes 1,6-hexanediol diacrylate, lauric acid acrylate, etc., which can reduce residual carbon elements during degreasing and ensure the density of the metal material.

Benefits of technology

The mechanical properties of photocured metal materials are comparable to those of commercially available forged metals, and the tribological properties are better than those of commercially available forged metals, while improving the dimensional accuracy and surface quality of metal parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638912A_ABST
    Figure CN119638912A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal additive manufacturing, in particular to photosensitive resin, photosensitive metal slurry and application thereof, a light-cured metal component and a preparation method and application thereof. The photosensitive resin provided by the invention is prepared from the following raw materials: a photosensitive resin monomer, a photosensitive resin prepolymer and a photoinitiator, the photosensitive resin monomer comprises a first photosensitive resin monomer, and the first photosensitive resin monomer comprises one or more of 1, 6-hexanediol diacrylate, lauric acid acrylate, 2-propoxy neopentyl glycol diacrylate and 1, 5-ethyoxyl trimethylolpropane triacrylate. When the photosensitive metal slurry prepared from the photosensitive resin is applied to photocuring 3D printing preparation of metal parts, the carbon residue problem caused by oxygen-free atmosphere degreasing treatment can be solved, carbide precipitation in a microstructure of a photocuring metal material is avoided, and therefore the mechanical property of the photocuring metal material is equivalent to that of commercially available forged metal; and the tribological property is superior to that of commercially available forged metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal additive manufacturing, and in particular to a photosensitive resin, a photosensitive metal slurry and applications thereof, a photocurable metal component and a preparation method and application thereof. Background Art

[0002] The continuous innovation and development of metal additive manufacturing technology has provided many possibilities for the processing and manufacturing of metal parts with complex shapes, fine structures, thin walls or porous parts. At present, the metal additive manufacturing technologies that have been widely studied in academia and widely used in industry mainly include powder bed melting and direct energy deposition. They use high-energy laser beams, electron beams or other heat sources to directly melt metal powders or wires and quickly solidify them, and print layer by layer until the entire part is manufactured. The metal raw materials undergo a rapid melting and solidification process, which can easily obtain fine-grained structures or non-equilibrium phases, and can obtain materials with higher hardness, tensile strength and yield strength than forged metals. However, instantaneous cooling will cause high residual stress and certain porosity inside the material, low elongation at break, and easy deformation and cracking. There are potential risks in service under some working conditions with high requirements for fatigue performance and reliability.

[0003] Photocuring technology is another important branch of additive manufacturing technology. It is currently mainly used for the molding and preparation of ceramic materials, especially white or light-colored ceramics such as aluminum oxide, zirconium oxide and silicon oxide. The main processes of this technology are the preparation of photosensitive metal slurry (composed of powder of the material to be cured, photosensitive resin, photoinitiator and various additives), 3D printing, degreasing (removing organic components such as photosensitive resin) and high-temperature sintering (to achieve the densification of powder). Its working principle is to use ultraviolet light to irradiate the photosensitive slurry, so that the liquid slurry is quickly solidified, and it is printed layer by layer until the entire part is formed. The material is then densified through degreasing and high-temperature sintering.

[0004] The photocuring technology for forming metal parts is an indirect forming technology. Compared with the rapid melting and rapid solidification process in powder bed fusion and direct energy deposition technology, the photocuring technology can avoid the stress, deformation, cracking and other problems caused by thermal shrinkage, reduce the pores in the material, and help reduce the burning loss of low-melting-point elements. In addition, the photocuring technology has the characteristics of high precision and high forming quality. The metal parts prepared by it are significantly better than those of powder bed fusion and direct energy deposition technology in terms of dimensional accuracy and surface roughness.

[0005] However, there are many technical difficulties in the photocuring technology to form metal materials, in order to achieve mechanical properties (density, tensile strength and elongation at break) and functionality (such as electrical conductivity, wear resistance, corrosion resistance, etc.) comparable to those of forged metals, and at the same time, the molded parts have high dimensional accuracy and surface accuracy. Most importantly, in order to prevent the oxidation of metal powders, the degreasing process of metal printing green blanks must be carried out in an oxygen-free atmosphere (such as an inert atmosphere such as argon or a non-reactive atmosphere such as nitrogen), which leads to incomplete decomposition of the photosensitive resin and residual carbon on the surface of the metal powder. It is difficult to completely remove the residual carbon in the subsequent sintering process, which has a destructive effect on the performance of the sintered metal material. For many metals, carbon is the most important alloying element. If the residual carbon problem cannot be solved, the plasticity, corrosion resistance and fatigue properties of the metal material will be greatly reduced. However, there is no report on how to solve the residual carbon problem. Summary of the invention

[0006] The purpose of the present invention is to provide a photosensitive resin, a photosensitive metal slurry and its application, a photocurable metal component and its preparation method and application. The photosensitive metal slurry prepared by the photosensitive resin is applied to the photocurable 3D printing preparation of metal parts, which can solve the carbon residue problem caused by the degreasing treatment in an oxygen-free atmosphere and avoid the precipitation of carbides in the microstructure of the photocurable metal material, so that the mechanical properties of the photocurable metal material are equivalent to those of the commercially available forged metal, and the tribological properties are better than those of the commercially available forged metal.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a photosensitive resin, the preparation raw materials of which include a photosensitive resin monomer, a photosensitive resin prepolymer and a photoinitiator; The photosensitive resin monomer includes a first photosensitive resin monomer, and the first photosensitive resin monomer includes one or more of 1,6-hexanediol diacrylate, lauric acid acrylate, 2-propoxy neopentyl glycol diacrylate and 1,5-ethoxy trimethylol propane triacrylate.

[0008] Preferably, the photosensitive resin monomer further comprises a second photosensitive resin monomer, and the mass ratio of the first photosensitive resin monomer to the second photosensitive resin monomer is (4-2): (1-3); The second photosensitive resin monomer includes one or more of isobornyl acrylate, 4-hydroxybutyl acrylate, 1,9-nonanediol diacrylate and acryloylmorpholine.

[0009] Preferably, the mass ratio of the photosensitive resin monomer to the photosensitive resin prepolymer is (7-5): (3-5); The photosensitive resin prepolymer is aliphatic polyurethane acrylate and / or modified polyurethane acrylate.

[0010] The present invention also provides a photosensitive metal slurry, comprising a photosensitive resin and a metal powder in a mass ratio of (25-7): (75-93); The photosensitive resin is the photosensitive resin described in the above technical solution.

[0011] Preferably, the particle size distribution range of the metal powder is 0-25 μm; The metal powder includes iron-based alloy powder, nickel-based alloy powder, titanium-based alloy powder or copper-based alloy powder.

[0012] The present invention also provides the use of the photosensitive metal slurry described in the above technical solution in 3D printing.

[0013] The present invention also provides a method for preparing a light-cured metal component, comprising the following steps: The photosensitive metal slurry is sequentially subjected to 3D printing, degreasing, residual carbon removal and sintering to obtain the photocurable metal component; The photosensitive metal slurry is the photosensitive metal slurry described in the above technical solution; The degreasing treatment is carried out in pure argon or argon-hydrogen mixed gas; The residual carbon removal and sintering treatment are independently carried out in an argon-hydrogen mixed gas or pure hydrogen.

[0014] Preferably, the degreasing process is as follows: heating from room temperature to 200-300°C at a heating rate of 0.2-2°C / min, and keeping the temperature for 30-120min; heating from 200-300°C to 400-500°C at a heating rate of 0.05-0.5°C / min, and keeping the temperature for 60-180min; finally heating from 400-500°C to 550-650°C at a heating rate of 0.2-2°C / min, and keeping the temperature for 30-120min; cooling to room temperature; The process of removing residual carbon is as follows: heating from room temperature to 550-650°C at a heating rate of 5-20°C / min, and keeping the temperature for 0-30min; heating from 550-650°C to 950-1050°C at a heating rate of 0.5-2.5°C / min, and keeping the temperature for 0-60min; The sintering process is as follows: heating the temperature from 950 to 1050° C. to the final sintering temperature at a heating rate of 0.5 to 1° C. / min, keeping the temperature for 4 to 8 hours, and then cooling to room temperature.

[0015] The present invention also provides a photocurable metal component prepared by the preparation method described in the above technical solution.

[0016] The present invention also provides the application of the photocurable metal component described in the above technical solution in the field of friction.

[0017] The present invention provides a photosensitive resin, the preparation raw materials include photosensitive resin monomer, photosensitive resin prepolymer and photoinitiator; the photosensitive resin monomer includes a first photosensitive resin monomer, and the first photosensitive resin monomer includes one or more of 1,6-hexanediol diacrylate, lauric acid acrylate, 2-propoxyneopentyl glycol diacrylate and 1,5-ethoxytrimethylolpropane triacrylate. When the photosensitive resin prepared by the specific photosensitive resin monomer used in the present invention is applied to the preparation of photocurable metal components, it can reduce the residual carbon elements generated on the surface of the metal powder by the decomposition of the photosensitive resin during the degreasing process, thereby making the mechanical properties of the prepared photocurable metal material equivalent to those of commercially available forged metals, and the tribological properties are better than those of commercially available forged metals; The present invention also provides a photosensitive metal slurry, comprising a photosensitive resin and a metal powder in a mass ratio of (25~7): (75~93); the photosensitive resin is the photosensitive resin described in the above technical solution. The photosensitive metal slurry described in the present invention has a relatively high slurry viscosity (50~200Pa·s) in a static state, which can slow down the sedimentation rate of the metal powder and ensure that the solid content of the metal powder is increased as much as possible under the premise of smooth printing; at the same time, the photosensitive metal slurry has obvious shear thinning characteristics and has a relatively low slurry viscosity during the slurry paving action (the viscosity range of the slurry paving process in the 3D printing process is 1~10Pa·s), which can ensure the smooth paving of the slurry and improve the quality and precision of the solidification molding; The present invention also provides a method for preparing a photocurable metal component, comprising the following steps: subjecting a photosensitive metal slurry to 3D printing, degreasing, residual carbon removal and sintering in sequence to obtain the photocurable metal component; the photosensitive metal slurry is the photosensitive metal slurry described in the above technical solution. The preparation method removes most of the photosensitive resin polymer by degreasing, and achieves the purpose of removing residual carbon through residual carbon removal and sintering processes, thereby avoiding the precipitation of carbides in the microstructure of the photocurable metal material, achieving the densification of the metal powder, and making the mechanical properties of the prepared photocurable metal material equivalent to those of commercially available forged metals, and the tribological properties are better than those of commercially available forged metals.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The mechanical properties of metal materials prepared by photocuring technology are comparable to those of commercially available wrought metals, and their tribological properties are better than those of commercially available wrought metals. Compared with the two more mature metal 3D printing technologies, powder bed fusion and direct energy deposition, metal parts prepared by photocuring technology have higher dimensional accuracy and surface quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The SEM image (a) and particle size distribution curve (b) of the sieved stainless steel powder in Example 1; Figure 2 The viscosity of the photosensitive metal paste described in Example 1 varies with shear rate; Figure 3 This is a schematic diagram of the printing principle of the light-curing 3D printing of the present invention; Figure 4 is the measured size of the rectangular photocurable metal component actually prepared in Example 1; Figure 5 The SEM photograph, three-dimensional morphology and surface roughness (a) of the photocurable metal component in the exposure plane and the SEM photograph, three-dimensional morphology and surface roughness (b) perpendicular to the exposure plane described in Example 1; Figure 6 The engineering stress-strain curves of the light-cured AISI 316L stainless steel and the commercially available forged AISI 316L stainless steel described in Example 1; Figure 7 The dynamic polarization curves of the light-cured AISI 316L stainless steel and the commercially available forged AISI 316L stainless steel described in Example 1; Figure 8 Friction coefficient curve (a) and wear rate (b) of the light-cured AISI 316L stainless steel and commercially available forged AISI 316L stainless steel in 3.5wt% NaCl aqueous solution in Example 1; Fig. 9 This is a physical picture of the light-cured AISI 316L stainless steel part described in Example 1; Fig.10 The engineering stress-strain curves of the light-cured AISI 316L stainless steel materials described in Examples 1 and 7; Fig.11 The engineering stress-strain curves of the light-cured AISI 316L stainless steel materials described in Comparative Example 1 and Example 1; Fig.12 The engineering stress-strain curves of the light-cured AISI 316L stainless steel materials described in Comparative Example 3 and Example 1; Fig.13 Metallographic microscope photos of the light-cured AISI 316L stainless steel material (a) described in Comparative Example 3 and the light-cured AISI 316L stainless steel material (b) described in Example 1. DETAILED DESCRIPTION

[0020] The present invention provides a photosensitive resin, the preparation raw materials of which include a photosensitive resin monomer, a photosensitive resin prepolymer and a photoinitiator; The photosensitive resin monomer includes a first photosensitive resin monomer, and the first photosensitive resin monomer includes one or more of 1,6-hexanediol diacrylate, lauric acid acrylate, 2-propoxy neopentyl glycol diacrylate and 1,5-ethoxy trimethylol propane triacrylate.

[0021] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0022] In the present invention, the first photosensitive resin monomer includes one or more of 1,6-hexanediol diacrylate (HDDA), lauric acid acrylate (LA), 2-propoxyneopentyl glycol diacrylate (2PO-NPGDA) and 15-ethoxytrimethylolpropane triacrylate (15EO-TMPTA). When the first photosensitive resin monomer is two or more of the above specific selections, the present invention has no special limitation on the ratio of the above specific substances, and they can be mixed in any ratio.

[0023] In the present invention, the photosensitive resin monomer preferably further includes a second photosensitive resin monomer, and the second photosensitive resin monomer preferably includes one or more of isobornyl acrylate (IBOA), 4-hydroxybutyl acrylate (4-HBA), 1,9-nonanediol diacrylate (NDDA) and acryloyl morpholine (ACMO). When the second photosensitive resin monomer is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio.

[0024] In the present invention, the mass ratio of the first photosensitive resin monomer to the second photosensitive resin monomer is preferably (4-2):(1-3), more preferably (3.5-2.5):(1.5-2.5), and most preferably (3.2-2.8):(1.8-2.2).

[0025] In the present invention, the photosensitive resin prepolymer is aliphatic polyurethane acrylate and / or modified polyurethane acrylate; the aliphatic polyurethane acrylate is preferably difunctional aliphatic polyurethane acrylate U600; the modified polyurethane acrylate is preferably modified difunctional polyurethane acrylate Easepi 864; when the photosensitive resin prepolymer is aliphatic polyurethane acrylate and modified polyurethane acrylate, the present invention has no special limitation on the ratio of the aliphatic polyurethane acrylate and the modified polyurethane acrylate, and they can be mixed in any ratio.

[0026] In the present invention, the mass ratio of the photosensitive resin monomer to the photosensitive resin prepolymer is preferably (7-5):(3-5), more preferably (6.8-5.2):(3.2-4.8), and most preferably (6.5-5.5):(3.5-4.5).

[0027] In the present invention, the purpose of controlling the mass ratio of the photosensitive resin monomer and the photosensitive resin prepolymer within the above range is to obtain a photosensitive resin with a higher viscosity, so that the metal slurry prepared after adding the metal powder has a higher viscosity, thereby achieving the purpose of slowing down the sedimentation rate of the metal powder and ensuring the smooth solidification and molding of the high-solid content metal slurry.

[0028] In the present invention, the photoinitiator preferably includes trimethylbenzoyldiphenylphosphine oxide; the mass percentage of the photoinitiator to the total mass of the photosensitive resin monomer and the photosensitive resin prepolymer is preferably 0.5-5%, more preferably 1-4.5%, and most preferably 1.5-4%.

[0029] In the present invention, the raw materials for preparing the photosensitive resin preferably further include a dispersant and a defoaming agent.

[0030] In the present invention, the dispersant preferably includes one or more of oleic acid, sodium dodecylbenzene sulfonate, polyacrylic acid, polycarboxylic acid and polyvinyl alcohol. When the dispersant is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In the present invention, the mass percentage of the mass of the dispersant to the total mass of the photosensitive resin monomer and the photosensitive resin prepolymer is preferably 0.1-3%, more preferably 0.5-2.3%, and most preferably 1.2-1.7%.

[0031] In the present invention, the defoamer preferably includes one or more of BYK-052N, ACP-1400, KSZ-108 and BYK-088. When the defoamer is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In the present invention, the mass percentage of the defoamer to the total mass of the photosensitive resin monomer and the photosensitive resin prepolymer is preferably 0.1-2%, more preferably 0.2-1.8%, and most preferably 0.4-1.5%.

[0032] In the present invention, the method for preparing the photosensitive resin preferably comprises the following steps: The photosensitive resin is obtained by mixing a photosensitive resin monomer, a photosensitive resin prepolymer and a photoinitiator.

[0033] In the present invention, the mixing is preferably to first mix the photosensitive resin monomer and the photosensitive resin prepolymer, then add the photoinitiator and stir. The stirring temperature is preferably 30-60°C, more preferably 35-50°C, and most preferably 40°C; the stirring speed is preferably 200-600r / min, more preferably 300-500r / min, and most preferably 400r / min; the stirring time is preferably 0.5-3h, more preferably 0.8-2h, and most preferably 1h.

[0034] After the mixing, the present invention also preferably includes adding a dispersant and a defoamer in sequence to the obtained mixture. The present invention does not have any special restrictions on the process of adding the dispersant and the defoamer, and the process well known to those skilled in the art can be used. In the present invention, after the addition of the dispersant and the defoamer is completed, stirring is also preferably included, and the stirring temperature is preferably 30~60°C, more preferably 35~50°C, and most preferably 40°C; the stirring speed is preferably 200~600r / min, more preferably 300~500r / min, and most preferably 400r / min. The time for adding the stirring is preferably 0.5~3h, more preferably 0.8~2h, and most preferably 1h.

[0035] In the present invention, the photosensitive resin has good light-curing performance and rheological properties, and high interlayer bonding strength.

[0036] The present invention also provides a photosensitive metal slurry, comprising a photosensitive resin and a metal powder in a mass ratio of (25-7): (75-93); The photosensitive resin is the photosensitive resin described in the above technical solution.

[0037] In the present invention, the particle size distribution range of the metal powder is preferably 0-25 μm. In an embodiment of the present invention, the metal powder is preferably obtained by vibrating and screening commercially available metal powder with a particle size of ≤30 μm. The vibrating and screening is preferably performed using a 1000 mesh screen.

[0038] In the present invention, the metal powder preferably includes iron-based alloy powder, nickel-based alloy powder, titanium-based alloy powder or copper-based alloy powder; the present invention does not have any special restrictions on the types of the iron-based alloy powder, nickel-based alloy powder, titanium-based alloy powder or copper-based alloy powder, and the types familiar to those skilled in the art can be used. In an embodiment of the present invention, the metal powder can be AISI 316L stainless steel powder, AISI 304L stainless steel powder, 17-4PH martensitic stainless steel powder, Inconel 625 nickel-based alloy powder, Ti6Al4V titanium alloy powder or pure copper powder.

[0039] In the present invention, the mass ratio of the photosensitive resin to the metal powder is preferably (25-7): (75-93), more preferably (23-8): (77-92), and most preferably (21-9): (79-91).

[0040] In the present invention, the method for preparing the photosensitive metal paste preferably comprises the following steps: The photosensitive resin and the metal powder are mixed and then homogenized to obtain the photosensitive metal slurry.

[0041] The present invention does not have any special limitation on the mixing process, and the mixing process may be carried out using a process well known to those skilled in the art.

[0042] In the present invention, the speed of the homogenization treatment is preferably 300-900 r / min, more preferably 400-800 r / min, and most preferably 500-700 r / min; the time of the homogenization treatment is preferably 1-10 min, more preferably 2-8 min, and most preferably 3-7 min; the homogenization treatment is preferably carried out under vacuum conditions, and the vacuum degree of the vacuum conditions is preferably 0-5 kPa, more preferably 0-3 kPa, and most preferably 0-1.3 kPa. In an embodiment of the present invention, the homogenization treatment is specifically carried out in a centrifugal homogenizer.

[0043] In the present invention, the homogenization treatment is used to achieve sufficient mixing of the metal powder and the photosensitive resin and to discharge bubbles in the photosensitive metal slurry.

[0044] The present invention also provides the use of the photosensitive metal slurry described in the above technical solution in 3D printing.

[0045] The present invention also provides a method for preparing a light-cured metal component, comprising the following steps: The photosensitive metal slurry is sequentially subjected to 3D printing, degreasing, residual carbon removal and sintering to obtain the photocurable metal component; The photosensitive metal slurry is the photosensitive metal slurry described in the above technical solution.

[0046] The present invention sequentially performs 3D printing, degreasing, residual carbon removal and sintering on the photosensitive metal slurry to obtain the light-cured metal component.

[0047] Before performing the 3D printing, the present invention also preferably includes a vacuum degassing treatment, wherein the vacuum degree of the vacuum degassing treatment is preferably 0-5 kPa, more preferably 0-3 kPa, and most preferably 0-1.3 kPa; the speed of the vacuum degassing treatment is preferably 300-900 r / min, more preferably 400-800 r / min, and most preferably 500-700 r / min; the time of the vacuum degassing treatment is preferably 1-6 min, more preferably 2-5 min, and most preferably 3-4 min. In an embodiment of the present invention, the vacuum degassing treatment is specifically performed in a centrifugal homogenizer.

[0048] In the present invention, the energy density of the light source for 3D printing is preferably 10-90 mW / cm 2 , more preferably 20~80mW / cm 2 , the most preferred is 30~60mW / cm 2 ; The exposure time is preferably 3~50s, more preferably 5~40s, and most preferably 10~30s; The printing thickness is preferably 15~50μm / layer, more preferably 18~45μm / layer, and most preferably 20~40μm / layer. In the present invention, the 3D printing preferably uses a digital light processing photocuring 3D printer. Compared with a stereolithography photocuring 3D printer, a digital light processing photocuring 3D printer has a higher printing efficiency and can reduce the risk of printing failure due to metal powder sedimentation. In the present invention, the digital light processing photocuring 3D printer is preferably equipped with a slurry real-time stirring and replenishing device. On the one hand, the photosensitive metal slurry is stirred in real time to prevent the metal powder from settling. On the other hand, the slurry in the slurry tank is replenished in time. The amount of slurry replenished is controlled by a liquid level sensor installed on the top of the slurry tank. The single replenishment amount should be as small as possible while ensuring that printing continues, further improving the problem of metal powder sedimentation in the photosensitive metal slurry (such as Figure 3 As shown). In the present invention, the unprinted photosensitive metal slurry is preferably stirred in real time during the 3D printing process. The present invention does not have any special limitation on the process of real-time stirring, and the process well known to those skilled in the art can be used. In the present invention, the real-time stirring can further improve the problem of metal powder sedimentation in the photosensitive metal slurry.

[0049] After the 3D printing is completed, the present invention also preferably includes cleaning and drying performed in sequence. In the present invention, the cleaning agent used for cleaning is preferably isopropyl alcohol. The present invention has no special limitation on the cleaning process, and the process well known to those skilled in the art can be used. The present invention has no special limitation on the drying process, and the process well known to those skilled in the art can be used.

[0050] In the present invention, the degreasing treatment is preferably carried out in pure argon or argon-hydrogen mixed gas, and the residual carbon removal and sintering treatment are independently preferably carried out in argon-hydrogen mixed gas or pure hydrogen. When the degreasing treatment, residual carbon removal and sintering treatment are carried out in argon-hydrogen mixed gas, the hydrogen content in the argon-hydrogen mixed gas is preferably 1-99%, more preferably 2-99%, and most preferably 3-99%. In the present invention, the gas flow rate of the pure argon, argon-hydrogen mixed gas or pure hydrogen is independently preferably 0.1-2L / min, more preferably 0.3-1.8L / min, and most preferably 0.5-1.5L / min. In the present invention, the control of the above-mentioned gas flow rate can keep the gas flow in a laminar state, which is conducive to more complete decomposition of the photosensitive resin and less residual carbon.

[0051] In the present invention, the degreasing treatment is preferably a step-by-step heating treatment, and the step-by-step heating process is preferably: heating from room temperature to 200-300°C at a heating rate of 0.2-2°C / min, and keeping warm for 30-120min; heating from 200-300°C to 400-500°C at a heating rate of 0.05-0.5°C / min, and keeping warm for 60-180min; finally, heating from 400-500°C to 550-650°C at a heating rate of 0.2-2°C / min, and keeping warm for 60-180min. The temperature of the reaction mixture is heated to 230-270°C for 30-120 min; the reaction mixture is cooled to room temperature with the furnace; more preferably, the temperature is increased from room temperature to 230-270°C at a heating rate of 0.5-1.5°C / min, and the temperature is kept for 60-90 min; the temperature is increased from 230-270°C to 430-470°C at a heating rate of 0.05-0.2°C / min, and the temperature is kept for 90-150 min; finally, the temperature is increased from 430-470°C to 570-630°C at a heating rate of 0.5-1.5°C / min, and the temperature is kept for 60-90 min; the reaction mixture is cooled to room temperature with the furnace; more preferably, the temperature is increased from room temperature to 230-270°C at a heating rate of 0.5-1.5°C / min, and the temperature is kept for 60-90 min.

[0052] In the present invention, the process of removing residual carbon is preferably carried out at a heating rate of 5 to 20°C / min, from room temperature to 550 to 650°C, and heat preservation for 0 to 30 minutes; at a heating rate of 0.5 to 2.5°C / min, from 550 to 650°C to 950 to 1050°C, and heat preservation for 0 to 60 minutes; more preferably at a heating rate of 10 to 15°C / min, from room temperature to 560 to 630°C, and heat preservation for 0 to 20 minutes; at a heating rate of 1.0 to 2.0°C / min, from 560 to 630°C to 980 to 1020°C, and heat preservation for 20 to 50 minutes. In the present invention, the above heating rate and heat preservation time can make the residual carbon element fully react with hydrogen (chemical equation is ), to fully remove the residual carbon.

[0053] In the present invention, the sintering process is preferably carried out at a heating rate of 0.5~1°C / min, from 950~1050°C to the final firing temperature, keeping the temperature for 4~8h, and then cooling to room temperature; more preferably, at a heating rate of 0.6~0.8°C / min, from 980~1020°C to the final firing temperature, keeping the temperature for 5~7h, and then cooling to room temperature. In the present invention, the final firing temperature is preferably 20~100°C less than the melting point of the metal powder in the photosensitive metal slurry. In the present invention, the cooling is preferably furnace cooling. In the present invention, the sintering treatment can achieve the purpose of metal densification, so that the prepared photocured metal components have the characteristics of high precision, excellent mechanical and friction properties.

[0054] The present invention also provides a photocurable metal component prepared by the preparation method described in the above technical solution.

[0055] The present invention also provides the application of the light-cured metal component described in the above technical solution in the field of friction. The present invention does not have any special limitation on the method of the application, and the method well known to those skilled in the art can be used.

[0056] The photosensitive resin, photosensitive metal paste and its application, photocurable metal component and its preparation method and application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0057] Example 1 According to the mass ratio of 2.5:1:2:4.5, the first photosensitive resin monomer LA (25g) and HDDA (10g), the second photosensitive resin monomer IBOA (20g) and the photosensitive resin prepolymer U600 (45g) were mixed, and 1g of the photoinitiator trimethylbenzoyldiphenylphosphine oxide (the amount is 1% of the total mass of LA, HDDA, IBOA and U600) was added, and the mixture was stirred for 1h at 40°C and 400r / min by a magnetic particle, and then 1g of the dispersant oleic acid (the amount is 1% of the total mass of LA, HDDA, IBOA and U600) was added, and the mixture was stirred for 1h at 40°C and 400r / min by a magnetic particle, and 0.3g of the defoaming agent BYK-052N (the amount is 0.3% of the total mass of LA, HDDA, IBOA and U600) was added, and the mixture was stirred for 1h at 40°C and 400r / min by a magnetic particle to obtain a photosensitive resin; The commercially available AISI 316L stainless steel powder with a particle size of ≤30 μm was sieved through a 1000-mesh sieve using a vibrating sieving machine to obtain the sieved stainless steel powder (SEM photo as shown in Figure 1 As shown in a in the figure, the particle size distribution curve is as follows Figure 1 As shown in b, Figure 1It can be seen that the sphericity of the sieved stainless steel powder is better, the surface is smooth and there is almost no satellite powder. The particle size of the sieved stainless steel powder is 3-25 μm, and the particle size distribution is Gaussian distribution. 10 6.4 μm, d 50 11.3 μm, d 90 is 18.8μm); The sieved stainless steel powder and the photosensitive resin were mixed in a mass ratio of 88:12, and homogenized in a centrifugal homogenizer (speed of 560 r / min, time of 3 min, vacuum degree of 1.3 kPa) to obtain a photosensitive metal slurry; The rheological properties of the photosensitive metal slurry were tested using a rotational rheometer. The test conditions were: a parallel disk module was selected, the disk diameter was 50 mm, the parallel disk gap was 0.5 mm, and the shear rate range was 0.01~1000 s -1 , the temperature is 25℃. Figure 2 is the viscosity variation curve of the photosensitive metal slurry with shear rate. Figure 2 It can be seen that the viscosity of the photosensitive metal slurry decreases with the increase of shear rate, and the viscosity of the photosensitive metal slurry shows obvious shear thinning behavior; when the photosensitive metal slurry is at rest (shear rate approaches 0), its viscosity is relatively high, about 112Pa·s, which means that the sedimentation rate of the metal powder in the photosensitive metal slurry is relatively slow, which is related to the high dosage of the photosensitive resin prepolymer. When the shear rate is 333s -1 (the shear rate value of the slurry during the slurry paving action in the 3D printing process), the viscosity value is relatively low, about 3.4 Pa·s, which is convenient for paving the photosensitive metal slurry, and is beneficial to improving the molding quality and precision of light-curing 3D printing; The photosensitive metal slurry was subjected to vacuum degassing treatment in a centrifugal homogenizer (rotation speed of 660 r / min, time of 3 min, vacuum degree of 1.3 kPa), and then subjected to photocuring 3D printing. A digital light processing photocuring 3D printer equipped with a slurry real-time stirring and replenishing device was selected (printing principle as shown in Figure 3 As shown in the figure), the parameters of the light-curing 3D printing are: the energy density of the light source is 45mW / cm 2 , the exposure time is 15s, the printing thickness is 25μm / layer, and the green blank of the metal part is obtained; After the green blank of the metal part is washed with isopropanol to remove the residual slurry and dried, it is degreased in a controlled atmosphere box furnace. The atmosphere of the degreasing treatment is an argon-hydrogen mixed gas with a hydrogen content of 5%. The gas flow rate is 0.5L / min to keep the gas flow in a laminar state. The degreasing process is to increase the temperature from room temperature to 250°C at a heating rate of 1°C / min and keep it warm for 60min; increase the temperature from 250°C to 450°C at a heating rate of 0.15°C / min and keep it warm for 120min; finally, increase the temperature from 450°C to 550°C at a heating rate of 0.5°C / min and keep it warm for 60min; cool it to room temperature with the furnace to obtain a brown blank of the metal part; The brown blank of the metal part is subjected to residual carbon removal in a tube furnace (the atmosphere used is an argon-hydrogen mixed gas with a hydrogen content of 5%, the gas flow rate is 0.5 L / min so that the gas flow is kept in a laminar state, and the process is to increase the temperature from room temperature to 550°C at a heating rate of 10°C / min, then increase the temperature from 550°C to 1000°C at a heating rate of 1.625°C / min, and keep the temperature for 30 minutes) and sintering treatment (the atmosphere used is an argon-hydrogen mixed gas with a hydrogen content of 5%, the gas flow rate is 0.5 L / min so that the gas flow is kept in a laminar state, and the process is to increase the temperature from 1000°C to 1380°C at a heating rate of 0.67°C / min, keep the temperature for 6 hours, and cool to room temperature with the furnace), to obtain a light-cured metal component with high precision and excellent mechanical and tribological properties (referred to as an AISI 316L stainless steel part); According to the preparation method of Example 1, the light-cured metal component is designed to be a cuboid, and the design dimensions of the length, width and height of the cuboid are 20 mm×15 mm×4 mm. The light-cured metal component actually prepared is measured, wherein Figure 4 is the measured size of the photocurable metal component actually prepared, Figure 4 It can be seen that the dimensional errors of the photocurable metal components in length, width and height are +0.35%, +0.20% and -0.25% respectively, which has a very high dimensional accuracy. Figure 5 The SEM photo, three-dimensional morphology and surface roughness (a) of the photocurable metal component in the exposure plane and the SEM photo, three-dimensional morphology and surface roughness (b) perpendicular to the exposure plane described in Example 1. Figure 5 It can be seen that in the exposure plane direction, its surface is smooth and flat, with a surface roughness of only 1.7μm. In the direction perpendicular to the exposure plane, its surface has a small amount of pores, and the surface roughness is 6.0μm. This shows that the metal components prepared by the photocuring technology have high surface quality both in the exposure plane and the side. The density of the light-cured metal component measured by the Archimedes drainage method is 7.65 g / cm 3, the density reached 95.9%. A room temperature tensile test (loading rate of 0.5 mm / min) was carried out on a universal mechanical testing machine to evaluate the mechanical properties of the photocured metal components, and compared with the commercially available forged AISI 316L stainless steel materials. The rectangular cross-section tensile specimens were directly printed using photocuring technology. After degreasing, sintering, grinding and polishing, the cross-sectional dimensions were approximately 3.3×2 mm and the parallel length was approximately 11 mm. The forged AISI 316L stainless steel tensile specimens were processed by an electric spark wire cutting machine, and the dimensions were consistent with the above dimensions. The engineering stress-strain curves of the above two specimens are shown in Figure 2. Figure 6 As shown by Figure 6 It can be seen that the tensile strength of the light-cured AISI 316L stainless steel material in Example 1 is 543 MPa, the yield strength is 180 MPa, and the elongation at break is 62%; the tensile strength of the commercially available forged AISI316L stainless steel material is 564 MPa, the yield strength is 185 MPa, and the elongation at break is 85%. The mechanical properties of the two materials are comparable; AISI 316L stainless steel has a wide range of applications in marine equipment, petrochemical and other industries due to its excellent corrosion resistance. Therefore, the use of photocuring technology to prepare AISI 316L stainless steel metal components needs to maintain its excellent corrosion resistance. The corrosion resistance is evaluated by the dynamic polarization curve measured by an electrochemical workstation. Ag / AgCl is selected as the reference electrode, the platinum electrode is used as the auxiliary electrode, the photocured AISI 316L stainless steel or the commercially available forged AISI 316L stainless steel is used as the working electrode, and the electrolyte is a 3.5wt% NaCl aqueous solution; the photocured AISI 316L or the commercially available forged AISI 316L is immersed in a 3.5wt% NaCl aqueous solution for 1h to stabilize its surface state, and then the dynamic polarization curve test is performed respectively. The scanning range of the working electrode relative to the reference electrode is -0.6V to +0.6V, and the scanning speed is 0.5mV / s. The dynamic polarization curves of the two materials are shown in Figure 2. Figure 7 As shown in Figure 1, the corrosion potential of the light-cured AISI 316L in Example 1 is -0.163 V, and the corrosion current density is 1.70×10 -7 A / cm 2 , compared with the corrosion potential of commercially available forged AISI 316L of -0.156 V and corrosion current density of 1.08×10 -7 A / cm 2 This indicates that the corrosion resistance of the light-cured AISI 316L material prepared by the present invention in a 3.5wt% NaCl aqueous solution is comparable to that of the commercially available forged AISI 316L material. The photocured AISI 316L stainless steel material or the commercially available forged AISI 316L stainless steel material was subjected to a corrosion friction performance test: the test was carried out on a reciprocating friction tester equipped with an electrochemical workstation, the corrosive medium was a 3.5wt% NaCl aqueous solution, Ag / AgCl was selected as the reference electrode, the platinum electrode was used as the auxiliary electrode, and the photocured AISI 316L stainless steel material or the commercially available forged AISI 316L stainless steel material was used as the working electrode. The light-cured AISI 316L stainless steel material or the commercially available forged AISI 316L stainless steel material performs reciprocating sliding motion relative to a stationary Si3N4 ball (with a diameter of 6 mm), with a sliding stroke of 10 mm, a load of 10 N, and a reciprocating frequency of 2 Hz. Before the test, the light-cured AISI 316L stainless steel material or the commercially available forged AISI 316L stainless steel material is immersed in a 3.5wt% NaCl aqueous solution for 10 min, and then a friction corrosion test is performed under an open circuit potential (OCP), with a sliding time of 40 min, and the material is left to stand for 10 min after unloading. The entire test lasts for 1 hour, and the electrochemical workstation automatically records the potential and current throughout the entire process; wherein Figure 8 The friction coefficient curve (a) and wear rate (b) of the light-cured AISI 316L stainless steel material and the commercially available forged AISI 316L stainless steel material in a 3.5wt% NaCl aqueous solution are shown in FIG. Figure 8 It can be seen that the friction coefficients of the light-cured AISI 316L stainless steel material and the commercially available forged AISI 316L stainless steel material are both about 0.45, but the wear rate of the light-cured AISI 316L stainless steel material is 31.8% lower than that of the commercially available forged AISI 316L stainless steel material, and its tribological performance is better than that of the commercially available forged AISI 316L stainless steel material.

[0058] Fig. 9 This is a photo of the light-cured AISI 316L stainless steel part prepared in Example 1. Fig. 9 It can be seen that the complex-shaped metal parts prepared by photocuring technology have high dimensional accuracy, low surface roughness, no deformation, warping, delamination and cracking, and there are 4 and 2 micropores with a diameter of 0.5 mm along the printing direction and perpendicular to the printing direction, respectively, with high shape accuracy. Compared with traditional metal forming methods such as casting, mold forming and machining, photocuring 3D printing technology has unique advantages in preparing complex shapes, containing internal channels, fine structures, thin walls or porous metal parts. It does not require mold opening, can be customized, has low cost and short production cycle, and provides a simple and efficient method for the manufacture of complex metal components.

[0059] Example 2 According to the mass ratio of 2:1:2:5, the first photosensitive resin monomer 2PO-NPGDA (20g) and LA (10g), the second photosensitive resin monomer ACMO (20g) and the photosensitive resin prepolymer Easepi 864 (50g) were mixed, and 1.5g of the photoinitiator trimethylbenzoyldiphenylphosphine oxide (the amount is 1.5% of the total mass of 2PO-NPGDA, LA, ACMO and Easepi 864) was added. After stirring for 1h at 40°C and 400r / min by a magnetic particle, 1g of the dispersant polyacrylic acid (the amount is 1% of the total mass of 2PO-NPGDA, LA, ACMO and Easepi 864) was added. After stirring for 1h at 40°C and 400r / min by a magnetic particle, 0.5g of the defoaming agent ACP-1400 (the amount is 2PO-NPGDA, LA, ACMO and Easepi 864 total mass), stirred by a magnetic stirrer at 40°C and 400 r / min for 1 h to obtain a photosensitive resin; The commercially available AISI 304L stainless steel powder with a particle size of ≤30 μm was sieved through a 1000-mesh sieve using a vibrating sieving machine to obtain sieved stainless steel powder; The sieved stainless steel powder and the photosensitive resin were mixed in a mass ratio of 87:13, and homogenized in a centrifugal homogenizer (speed of 560 r / min, time of 3 min, vacuum degree of 1.3 kPa) to obtain a photosensitive metal slurry; The photosensitive metal slurry was subjected to vacuum degassing treatment in a centrifugal homogenizer (speed of 660 r / min, time of 3 min, vacuum degree of 1.3 kPa), and then subjected to photocuring 3D printing. A digital light processing photocuring 3D printer equipped with a real-time slurry stirring and replenishing device was selected. The parameters of the photocuring 3D printing were: the energy density of the light source was 45 mW / cm 2 , the exposure time is 18s, the printing thickness is 25μm / layer, and the green blank of the metal part is obtained; After the green blank of the metal part is washed with isopropanol to remove the residual slurry and dried, it is degreased in a controlled atmosphere box furnace. The atmosphere of the degreasing treatment is pure argon gas, and the gas flow rate is 1L / min to keep the gas flow in a laminar state. The process of the degreasing treatment is to increase the temperature from room temperature to 250°C at a heating rate of 1.5°C / min and keep it warm for 50min; increase the temperature from 250°C to 450°C at a heating rate of 0.2°C / min and keep it warm for 120min; finally, increase the temperature from 450°C to 600°C at a heating rate of 1°C / min and keep it warm for 60min; cool it to room temperature with the furnace to obtain a brown blank of the metal part; The brown blank of the metal part is subjected to residual carbon removal in a tubular furnace (the atmosphere used is pure hydrogen, the gas flow rate is 1 L / min so that the gas flow remains in a laminar state, the process is to increase the temperature from room temperature to 600°C at a heating rate of 10°C / min, then increase the temperature from 600°C to 1000°C at a heating rate of 2.5°C / min, and keep warm for 30 minutes) and sintering treatment (the atmosphere used is pure hydrogen, the gas flow rate is 1 L / min so that the gas flow remains in a laminar state, the process is to increase the temperature from 1000°C to 1360°C at a heating rate of 0.8°C / min, keep warm for 7 hours, and cool to room temperature with the furnace), to obtain a light-cured metal component with high precision and excellent mechanical and tribological properties (referred to as an AISI 304L stainless steel part).

[0060] Example 3 According to the mass ratio of 2:1.5:2:4.5, the first photosensitive resin monomer HDDA (20g) and 15EO-TMPTA (15g), the second photosensitive resin monomer IBOA (20g) and the photosensitive resin prepolymer U600 (45g) were mixed, and 1g of the photoinitiator trimethylbenzoyl diphenylphosphine oxide (the amount used was 1% of the total mass of HDDA, 15EO-TMPTA, IBOA and U600) was added, and the mixture was stirred at 40°C and 400r / min by a magnetic stirrer. After stirring for 1 hour, 1 g of dispersant oleic acid (the amount used is 1% of the total mass of HDDA, 15EO-TMPTA, IBOA and U600) was added, and the mixture was stirred for 1 hour at 40°C and 400 r / min by a magnetic particle, and 0.5 g of defoamer BYK-052N (the amount used is 0.5% of the total mass of HDDA, 15EO-TMPTA, IBOA and U600) was added, and the mixture was stirred for 1 hour at 40°C and 400 r / min by a magnetic particle to obtain a photosensitive resin; The commercially available 17-4PH martensitic stainless steel powder with a particle size of ≤30 μm is sieved through a 1000-mesh sieve using a vibrating sieving machine to obtain sieved martensitic stainless steel powder; The sieved martensitic stainless steel powder and the photosensitive resin were mixed in a mass ratio of 86:14, and homogenized in a centrifugal homogenizer (speed of 560 r / min, time of 3 min, vacuum degree of 1.3 kPa) to obtain a photosensitive metal slurry; The photosensitive metal slurry was subjected to vacuum degassing treatment in a centrifugal homogenizer (speed of 660 r / min, time of 3 min, vacuum degree of 1.3 kPa), and then subjected to photocuring 3D printing. A digital light processing photocuring 3D printer equipped with a real-time slurry stirring and replenishing device was selected. The parameters of the photocuring 3D printing were: the energy density of the light source was 50 mW / cm 2 , the exposure time is 20s, the printing thickness is 25μm / layer, and the green blank of the metal part is obtained; After the green blank of the metal part is washed with isopropanol to remove the residual slurry and dried, it is degreased in a controlled atmosphere box furnace. The atmosphere of the degreasing treatment is an argon-hydrogen mixed gas with a hydrogen content of 5%. The gas flow rate is 0.5L / min to keep the gas flow in a laminar state. The degreasing process is to increase the temperature from room temperature to 250°C at a heating rate of 1°C / min and keep it warm for 60min; increase the temperature from 250°C to 470°C at a heating rate of 0.3°C / min and keep it warm for 180min; finally, increase the temperature from 470°C to 650°C at a heating rate of 1.5°C / min and keep it warm for 60min; cool it to room temperature with the furnace to obtain a brown blank of the metal part; The brown blank of the metal part is subjected to residual carbon removal in a tubular furnace (the atmosphere used is an argon-hydrogen mixed gas with a hydrogen content of 10%, the gas flow rate is 0.5 L / min so that the gas flow is kept in a laminar state, and the process is to increase the temperature from room temperature to 650°C at a heating rate of 10°C / min, then increase the temperature from 650°C to 950°C at a heating rate of 1°C / min, and keep warm for 60 minutes) and sintering treatment (the atmosphere used is an argon-hydrogen mixed gas with a hydrogen content of 10%, the gas flow rate is 0.5 L / min so that the gas flow is kept in a laminar state, and the process is to increase the temperature from 950°C to 1370°C at a heating rate of 0.75°C / min, keep warm for 6.5 hours, and cool to room temperature with the furnace), to obtain a light-cured metal component with high precision and excellent mechanical and tribological properties (referred to as a 17-4PH martensitic stainless steel part).

[0061] Example 4 According to the mass ratio of 2.5:1.5:1.5:4.5, the first photosensitive resin monomer HDDA (25g) and LA (15g), the second photosensitive resin monomer ACMO (15g) photosensitive resin prepolymer Easepi 864 (45g) were mixed, and 1.5g of the photoinitiator trimethylbenzoyl diphenyl phosphine oxide (the amount is 1.5% of the total mass of HDDA, LA, ACMO and Easepi 864) was added, and after stirring for 1h at 40℃ and 400r / min by a magnetic particle, 1g of the dispersant polyacrylic acid (the amount is 1% of the total mass of HDDA, LA, ACMO and Easepi 864) was added, and stirred for 1h at 40℃ and 400r / min by a magnetic particle, 0.5g of the defoaming agent ACP-1400 (the amount of HDDA, LA, ACMO and Easepi 864 total mass), stirred by a magnetic stirrer at 40°C and 400 r / min for 1 h to obtain a photosensitive resin; The commercially available Inconel 625 nickel-based alloy powder with a particle size of ≤30 μm is sieved through a 1000-mesh sieve using a vibrating sieving machine to obtain a sieved nickel-based alloy powder; The screened nickel-based alloy powder and the photosensitive resin are mixed in a mass ratio of 91:9, and homogenized in a centrifugal homogenizer (speed of 560 r / min, time of 3 min, vacuum degree of 1.3 kPa) to obtain a photosensitive metal slurry; The photosensitive metal slurry was subjected to vacuum degassing treatment in a centrifugal homogenizer (speed of 660 r / min, time of 3 min, vacuum degree of 1.3 kPa), and then subjected to photocuring 3D printing. A digital light processing photocuring 3D printer equipped with a real-time slurry stirring and replenishing device was selected. The parameters of the photocuring 3D printing were: the energy density of the light source was 55 mW / cm 2 , the exposure time is 15s, the printing thickness is 20μm / layer, and the green blank of the metal part is obtained; After the green blank of the metal part is washed with isopropanol to remove the residual slurry and dried, it is degreased in a controlled atmosphere box furnace. The atmosphere of the degreasing treatment is an argon-hydrogen mixed gas with a hydrogen content of 5%. The gas flow rate is 0.5L / min to keep the gas flow in a laminar state. The degreasing process is to increase the temperature from room temperature to 220°C at a heating rate of 1.5°C / min and keep it warm for 45min; increase the temperature from 220°C to 450°C at a heating rate of 0.2°C / min and keep it warm for 120min; finally, increase the temperature from 450°C to 550°C at a heating rate of 1°C / min and keep it warm for 60min; cool it to room temperature with the furnace to obtain a brown blank of the metal part; The brown blank of the metal part is subjected to residual carbon removal in a tubular furnace (the atmosphere used is pure hydrogen, the gas flow rate is 1 L / min so that the gas flow is kept in a laminar state, and the process is to increase the temperature from room temperature to 550°C at a heating rate of 10°C / min, and then increase the temperature from 550°C to 1000°C at a heating rate of 2°C / min) and sintering treatment (the atmosphere used is pure hydrogen, the gas flow rate is 0.5 L / min so that the gas flow is kept in a laminar state, and the process is to increase the temperature from 1000°C to 1260°C at a heating rate of 0.7°C / min, keep warm for 6 hours, and cool to room temperature with the furnace), to obtain a light-cured metal component (denoted as Inconel 625 nickel-based alloy part) with high precision and excellent mechanical and tribological properties.

[0062] Example 5 According to the mass ratio of 2:2:1:5, the first photosensitive resin monomer HDDA (20g) and 2PO-NPGDA (20g), the second photosensitive resin monomer IBOA (10g) and the photosensitive resin prepolymer Easepi 864 (50g) were mixed, and 1g of the photoinitiator trimethylbenzoyldiphenylphosphine oxide (the amount is 1% of the total mass of HDDA, 2PO-NPGDA, IBOA and Easepi 864) was added. After stirring for 1h at 40°C and 400r / min by a magnetic particle, 1g of the dispersant oleic acid (the amount is 1% of the total mass of HDDA, 2PO-NPGDA, IBOA and Easepi 864) was added. After stirring for 1h at 40°C and 400r / min by a magnetic particle, 0.2g of the defoaming agent ACP-1400 (the amount of HDDA, 2PO-NPGDA, IBOA and Easepi 864 total mass), stirred by a magnetic stirrer at 40°C and 400 r / min for 1 h to obtain a photosensitive resin; The commercially available Ti6Al4V titanium alloy powder with a particle size of ≤30 μm is sieved through a 1500-mesh sieve using a vibrating sieving machine to obtain sieved titanium alloy powder; The screened titanium alloy powder and the photosensitive resin are mixed in a mass ratio of 79:21, and homogenized in a centrifugal homogenizer (speed of 560 r / min, time of 3 min, vacuum degree of 1.3 kPa) to obtain a photosensitive metal slurry; The photosensitive metal slurry was subjected to vacuum degassing treatment in a centrifugal homogenizer (speed of 660 r / min, time of 3 min, vacuum degree of 1.3 kPa), and then subjected to photocuring 3D printing. A digital light processing photocuring 3D printer equipped with a real-time slurry stirring and replenishing device was selected. The parameters of the photocuring 3D printing were: the energy density of the light source was 45 mW / cm 2 , the exposure time is 14s, the printing thickness is 20μm / layer, and the green blank of the metal part is obtained; After the green blank of the metal part is washed with isopropanol to remove the residual slurry and dried, it is degreased in a controlled atmosphere box furnace. The atmosphere of the degreasing treatment is an argon-hydrogen mixed gas with a hydrogen content of 15%. The gas flow rate is 0.5L / min to keep the gas flow in a laminar state. The degreasing process is to increase the temperature from room temperature to 240°C at a heating rate of 1°C / min and keep it warm for 60min; increase the temperature from 240°C to 450°C at a heating rate of 0.15°C / min and keep it warm for 120min; finally, increase the temperature from 450°C to 600°C at a heating rate of 0.5°C / min and keep it warm for 60min; cool it to room temperature with the furnace to obtain a brown blank of the metal part; The brown blank of the metal part is subjected to residual carbon removal in a tubular furnace (the atmosphere used is an argon-hydrogen mixed gas with a hydrogen content of 50%, the gas flow rate is 0.5 L / min so that the gas flow remains in a laminar state, and the process is to increase the temperature from room temperature to 600°C at a heating rate of 10°C / min, and then increase the temperature from 600°C to 950°C at a heating rate of 1.5°C / min) and sintering treatment (the atmosphere used is an argon-hydrogen mixed gas with a hydrogen content of 50%, the gas flow rate is 0.5 L / min so that the gas flow remains in a laminar state, and the process is to increase the temperature from 950°C to 1600°C at a heating rate of 1°C / min, keep warm for 4 hours, and cool to room temperature with the furnace), to obtain a light-cured metal component (denoted as a Ti6Al4V titanium alloy part) with high precision and excellent mechanical and tribological properties.

[0063] Example 6 The first photosensitive resin monomer 15EO-TMPTA (25 g) and LA (15 g), the second photosensitive resin monomer ACMO (25 g) and the photosensitive resin prepolymer U600 (35 g) were mixed in a mass ratio of 2.5:1.5:2.5:3.5, and 2 g of the photoinitiator trimethylbenzoyl diphenylphosphine oxide (the amount used was 2% of the total mass of 15EO-TMPTA, LA, ACMO and U600) was added. The mixture was stirred at 40 ° C and 400 r / min by a magnetic stirrer. After stirring for 1 hour under the conditions of stirring for 1 hour, 1 g of dispersant polyacrylic acid (the amount used is 1% of the total mass of 15EO-TMPTA, LA, ACMO and U600) was added, and stirred for 1 hour at 40°C and 400 r / min by a magnetic particle, 0.4 g of defoaming agent BYK-088 (the amount used is 0.4% of the total mass of 15EO-TMPTA, LA, ACMO and U600) was added, and stirred for 1 hour at 40°C and 400 r / min by a magnetic particle, to obtain a photosensitive resin; The commercially available pure copper powder with a particle size of ≤30 μm is sieved through a 1000-mesh sieve using a vibrating sieving machine to obtain sieved pure copper powder; The screened pure copper powder and the photosensitive resin are mixed in a mass ratio of 87:13, and homogenized in a centrifugal homogenizer (speed of 560 r / min, time of 3 min, vacuum degree of 1.3 kPa) to obtain a photosensitive metal slurry; The photosensitive metal slurry was subjected to vacuum degassing treatment in a centrifugal homogenizer (speed of 660 r / min, time of 3 min, vacuum degree of 1.3 kPa), and then subjected to photocuring 3D printing. A digital light processing photocuring 3D printer equipped with a real-time slurry stirring and replenishing device was selected. The parameters of the photocuring 3D printing were: the energy density of the light source was 50 mW / cm 2 , the exposure time is 18s, the printing thickness is 25μm / layer, and the green blank of the metal part is obtained; After the green blank of the metal part is washed with isopropanol to remove the residual slurry and dried, it is degreased in a controlled atmosphere box furnace. The atmosphere of the degreasing treatment is an argon-hydrogen mixed gas with a hydrogen content of 5%. The gas flow rate is 0.5L / min to keep the gas flow in a laminar state. The process of the degreasing treatment is to increase the temperature from room temperature to 250°C at a heating rate of 1°C / min and keep it warm for 60min; to increase the temperature from 250°C to 430°C at a heating rate of 0.1°C / min and keep it warm for 120min; finally, to increase the temperature from 430°C to 550°C at a heating rate of 0.5°C / min and keep it warm for 60min; and to cool to room temperature with the furnace to obtain a brown blank of the metal part; The brown blank of the metal part is subjected to residual carbon removal in a tubular furnace (the atmosphere used is pure hydrogen, the gas flow rate is 0.5 L / min so that the gas flow remains in a laminar state, and the process is to increase the temperature from room temperature to 550°C at a heating rate of 10°C / min, and then increase the temperature from 550°C to 950°C at a heating rate of 2.5°C / min) and sintering treatment (the atmosphere used is pure hydrogen, the gas flow rate is 0.65 L / min so that the gas flow remains in a laminar state, and the process is to increase the temperature from 950°C to 1050°C at a heating rate of 1°C / min, keep warm for 5 hours, and cool to room temperature with the furnace), to obtain a light-cured metal component (referred to as a pure copper part) with high precision and excellent mechanical and tribological properties.

[0064] Example 7 Refer to Example 1, except that the sintering time is 2 hours to obtain a photocured metal component.

[0065] The density of the photocurable metal component was measured by the Archimedes drainage method and was 7.20 g / cm 3 The density is only 90.2%, which is significantly lower than the density of 95.9% of the photocurable metal component described in Example 1. Fig.10 The engineering stress-strain curves of the light-cured AISI 316L stainless steel materials prepared in Example 1 and Example 7 are compared. Fig.10 It can be seen that the tensile strength of the light-cured AISI 316L stainless steel material in Example 7 is 495 MPa, the yield strength is 149 MPa, and the elongation at break is 53%, which are respectively reduced to 91%, 83% and 85% of the tensile strength, yield strength and elongation at break of the light-cured AISI 316L stainless steel material in Example 1. This is because the holding time of the sintering treatment is short, and the diffusion between the metal powders is not sufficient, resulting in a high porosity and a low density of the material, which in turn reduces the tensile strength, yield strength and elongation at break of the material.

[0066] Comparative Example 1 Referring to Example 1, the difference is that the raw material for preparing the photosensitive resin, in addition to the first photosensitive resin monomer HDDA, the second photosensitive resin monomer IBOA and the photosensitive resin prepolymer U600, also contains a certain proportion of OPPEA, wherein the mass ratio of HDDA, OPPEA, IBOA and U600 is 1:2.5:2:4.5, and a photocurable metal component is prepared; Table 1 lists the carbon residue rates of several commonly used photosensitive resin monomers after thermal weight loss after photocuring. The heating temperature range of the thermal weight loss test is from room temperature to 800°C, the heating rate is 10°C / min, and the atmosphere is nitrogen. It can be seen from Table 1 that the carbon residue rates of the four photosensitive resin monomers HDDA, LA, 2PO-NPGDA and 15EO-TMPTA are relatively low, all below 5%, while the carbon residue rates of ACMO, OPPEA and TMPTA are relatively high, all around 10%.

[0067] Table 1 Carbon residue rate of commonly used photosensitive resin monomers after thermal weight loss after photocuring

[0068] Fig.11 The engineering stress-strain curves of the light-cured AISI 316L stainless steel material prepared in Example 1 and Comparative Example 1 are compared. Fig.11 It can be seen that the tensile strength, yield strength and elongation at break of the light-cured AISI 316L stainless steel material described in Comparative Example 1 will all drop significantly, with a tensile strength of 350MPa, a yield strength of 133MPa and an elongation at break of 40%. This is because the photosensitive resin formula contains 25wt% OPPEA, and too much carbon remains on the surface of the metal powder after degreasing. Even if the residual carbon is removed and sintering is performed subsequently, the carbon element cannot be completely removed, which results in a certain amount of carbide precipitating at the grain boundaries of the microstructure of the sintered metal material, causing the brittleness of the metal material to increase and the plasticity to decrease, so the tensile strength, yield strength and elongation at break will all drop significantly.

[0069] Comparative Example 2 Referring to Example 1, the difference is that the second photosensitive resin monomer IBOA is not added, the mass ratio of the first photosensitive resin monomer LA and HDDA, and the photosensitive resin prepolymer U600 is 3.1:1.3:5.6, and the prepared photosensitive metal slurry is used for 3D printing. As a result, printing failure occurs. This is mainly because the molecular formulas of the photosensitive resins LA and U600 both contain relatively long straight-chain alkyl groups, and the steric hindrance effect of the active acrylate groups between adjacent molecules is relatively large, the contact probability is reduced, and the difficulty of the photopolymerization reaction is increased. In addition, the photosensitive resin component lacks IBOA, which leads to weak interfacial bonding between adjacent cured layers, causing printing failure.

[0070] Comparative Example 3 Refer to Example 1, except that the atmosphere for removing residual carbon and sintering is changed to a vacuum environment, and a light-cured metal component is prepared; Fig.12 The engineering stress-strain curves of the light-cured AISI 316L stainless steel material described in Example 1 and Comparative Example 3 are compared. Fig.12 It can be seen that the tensile strength of the light-cured AISI 316L stainless steel material prepared in a vacuum environment is only 310MPa (a significant decrease of 42.9% compared with Example 1), and the elongation at break is only 4% (a significant decrease of 90.6% compared with Example 1), which can no longer meet the requirements of engineering applications. This is because there is a lack of hydrogen during the residual carbon removal and sintering process. The residual carbon element cannot be removed at high temperature, but continues to remain inside the material, resulting in the residual carbon element reacting with the metal element to form carbides after the material is sintered, and precipitating at the grain boundary to form a brittle phase. In addition, the precipitated phase hinders the movement of dislocations. The combined effect of the two increases the overall brittleness of the material.

[0071] Fig.13 Metallographic microscope photos of the light-cured AISI 316L stainless steel material (a) described in Comparative Example 3 and the light-cured AISI 316L stainless steel material (b) described in Example 1; Fig.13 (a) It can be seen that when the residual carbon cannot be removed, a large amount of carbide brittle phase precipitates at the grain boundaries of the AISI 316L austenite grains.

[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A photosensitive resin, characterized in that: The preparation raw materials include photosensitive resin monomer, photosensitive resin prepolymer and photoinitiator; The photosensitive resin monomer includes a first photosensitive resin monomer, and the first photosensitive resin monomer includes one or more of 1,6-hexanediol diacrylate, lauric acid acrylate, 2-propoxy neopentyl glycol diacrylate and 1,5-ethoxy trimethylol propane triacrylate.

2. The photosensitive resin according to claim 1, characterized in that The photosensitive resin monomer further includes a second photosensitive resin monomer, and the mass ratio of the first photosensitive resin monomer to the second photosensitive resin monomer is (4-2): (1-3); The second photosensitive resin monomer includes one or more of isobornyl acrylate, 4-hydroxybutyl acrylate, 1,9-nonanediol diacrylate and acryloylmorpholine.

3. The photosensitive resin according to claim 1, characterized in that The mass ratio of the photosensitive resin monomer to the photosensitive resin prepolymer is (7-5): (3-5); The photosensitive resin prepolymer is aliphatic polyurethane acrylate and / or modified polyurethane acrylate.

4. A photosensitive metal paste, characterized in that: It includes a photosensitive resin and a metal powder in a mass ratio of (25-7): (75-93); The photosensitive resin is the photosensitive resin according to any one of claims 1 to 3.

5. The photosensitive metal paste according to claim 4, characterized in that: The particle size distribution range of the metal powder is 0-25 μm; The metal powder includes iron-based alloy powder, nickel-based alloy powder, titanium-based alloy powder or copper-based alloy powder.

6. Use of the photosensitive metal slurry according to claim 4 or 5 in 3D printing.

7. A method for preparing a light-cured metal component, characterized in that: The following steps are involved: The photosensitive metal slurry is sequentially subjected to 3D printing, degreasing, residual carbon removal and sintering to obtain the photocurable metal component; The photosensitive metal paste is the photosensitive metal paste according to claim 4 or 5; The degreasing treatment is carried out in pure argon or argon-hydrogen mixed gas; The residual carbon removal and sintering treatment are independently carried out in an argon-hydrogen mixed gas or pure hydrogen.

8. The preparation method according to claim 7, characterized in that: The degreasing process is as follows: the temperature is increased from room temperature to 200-300°C at a heating rate of 0.2-2°C / min, and kept at a temperature of 30-120min; the temperature is increased from 200-300°C to 400-500°C at a heating rate of 0.05-0.5°C / min, and kept at a temperature of 60-180min; finally, the temperature is increased from 400-500°C to 550-650°C at a heating rate of 0.2-2°C / min, and kept at a temperature of 30-120min; and cooled to room temperature; The process of removing residual carbon is as follows: heating from room temperature to 550-650°C at a heating rate of 5-20°C / min, and keeping the temperature for 0-30min; heating from 550-650°C to 950-1050°C at a heating rate of 0.5-2.5°C / min, and keeping the temperature for 0-60min; The sintering process is as follows: heating the temperature from 950 to 1050° C. to the final sintering temperature at a heating rate of 0.5 to 1° C. / min, keeping the temperature for 4 to 8 hours, and then cooling to room temperature.

9. The photocurable metal component prepared by the preparation method according to claim 7 or 8.

10. Use of the photocurable metal component according to claim 9 in the field of friction.

Citation Information

Patent Citations

  • Method for photocuring 3D printing by using solid-state cured photosensitive resin

    CN111251603A

  • 3d printing method for manufacturing metal part or ceramic part through resin

    CN112439901A

  • Surface treatment method for metal powder injection molding pre-sintered blank

    CN113560573A

  • Metal slurry for photocuring 3D printing and preparation method thereof

    CN113600808A

  • Metal structural part and preparation method thereof

    CN114406269A